Novel association between STAT3 gene variant and vitiligo: A case-control study - Vaibhav Venkatesh; Deena C Mendez; T S Rajashekar; Sharath Balakrishna (Wolters Kluwer Medknow Publications, 2022)
Background: Vitiligo is an autoimmune disorder involving inflammatory damage to melanocytes. STAT3 genetic variant (rs744166 T > C) increases inflammatory signaling via JAK/STAT pathway. Aim: The purpose of this study was to check whether this translates into an association between vitiligo and STAT3 gene variant (rs744166 T > C). Materials and Methods: This is a case-control study. A total of 56 vitiligo patients and 90 healthy, age and gender-matched volunteers were recruited for the study. The STAT3 gene variant (rs744166 T > C) was genotyped using the restriction fragment length polymorphism method. Results: The frequency of the minor allele 'C' was higher in vitiligo patients (72.3%) than in healthy volunteers (57.8%). The difference between the two groups was statistically significant (P = 0.006; OR = 1.9 with 95% CI). The genotypic variant showed the highest association with vitiligo in the dominant model (P = 0.001). Conclusion: This study shows that the STAT3 gene variant (rs744166 T > C) is associated with vitiligo. This observation underlines the importance of the JAK/STAT signaling pathway in vitiligo pathogenesis.